Treatment modalities in primary gastric lymphoma: effect of rituximab and surgical treatment. A study by the Anatolian Society of Medical Oncology - Mehmet, Kucukoner; Sener, Cihan; Uyeturk, Ummugul; Seker, Mesut; Tastekin, Didem; Tonyali, Onder; Balakan, Ozan; Yazici, Omer Kemal; UrakcI, Zuhat; Isikdogan, Abdurrahman; Ozdemir, Nuriye; Inal, Ali; et al. (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : Gastrointestinal lymphoma is the most common type of extranodal lymphoma and commonly involved site is the stomach. We have compared the superiority between treatment modalities for primary gastric lymphoma and we want to investigate efficacy of rituximab in gastric lymphoma. Material and methods : Between April 2002 and December 2011, 146 patients with a histologically confirmed primary gastric lymphoma, initially diagnosed at eight different Cancer Centers within Turkey were evaluated retrospectively. According to the treatment modality, the patients were divided into chemotherapy (CT) alone, chemotherapy and radiotherapy (CRT), surgery and chemotherapy (SCT), surgery along with chemotherapy and radiotherapy (SCRT), and surgery (S) alone groups. Results: Median follow-up period was 25.5 months. The 5-year EFS (event free survival) and OS (overall survival) rates for the patients were 55% and 62.3% respectively. In Log rank analysis of OS and EFS, we have identified levels of albumin and hemoglobine, IPI score, stage at diagnosis as factors influencing survival. In multivariate analysis of OS and EFS, only albumin and stage at diagnosis were factors independently contributing to survival. There was no statistically significant difference in terms of survival between different treatment modalities (p = 0.707 in EFS and p = = 0.124 in OS). In analysis of patients treated with chemotherapy alone, there was no a statistically significant difference in terms of EFS and OS between chemotherapy regimens with or without rituximab in localized and advanced stage groups (p = 0.264 and p = 0.639). There was no statistical difference in survival rate (EFS and OS) between surgical or non-surgical treatment modalities for localized/advanced stage gastric lymphoma groups (p = 0.519 / p = 0.165). Conclusions : There are several treatment options due to similar results in different treatment modalities. Also benefit of rituximab treatment in gastric lymphoma is still a controversial subject. Additional prospective trials are definitely required in order to clarify use of rituximab in treatment of extranodal gastric lymphoma.